(untitled) (Research, Society and Development, 2019)
The present research aims to describe the strategies used to carry out an activity script with the aim of guiding an interaction with a virtual laboratory simulation. In this sense, a survey and analysis of some variables and elements of the gamification used to involve the subject in their daily activities were carried out. The gamification can influence the level of motivation, engagement, commitment and satisfaction of the individual when implementing elements of the games in a context external to the games. The elements of the games can be the obtaining of immediate feedbacks, competitiveness, bonuses, teamwork, leadership, repetitiveness etc. Finally, gamification makes it possible the interdisciplinarity, being possible to be applied in several contexts and in the daily life of the individuals.